Shear strength of fiber-reinforced high-strength steel ultra-high-performance concrete beams based on refined calculation of compression zone depth considering concrete tension. Issue 8 (June 2019) - Qi, Jianan; Ding, Xiaomeng; Wang, Zhen; Hu, Yuqing
This article presents an experimental and theoretical investigation on the shear behavior of fiber-reinforced ultra-high-performance concrete beams reinforced with high-strength steel. The test parameters included the fiber volume fraction, fiber type, and stirrup ratio. The test results indicate that the shear failure in ultra-high-performance concrete beams is not brittle and catastrophic but has ductility characteristics. A moderate quantity of stirrups can significantly improve the shear behavior of ultra-high-performance concrete beams, as reflected in the thorough propagation of cracks in both shear span and pure bending zone. The depth of the compression zone considering concrete tension was derived based on the deformation compatibility and force equilibrium equations for both serviceability limit state and ultimate limit state. The comparison of the proposed method and classical beam theory shows that the concrete tension should not be neglected in the serviceability limit state analysis. After cracking, the concrete tension can be neglected for simplicity when the beam is heavily reinforced and should be considered when the beam is lightly reinforced. Then, a shear strength model was established based on Rankine's failure criteria, the truss model, and Association Francaise de Génie Civil-Sétra. Finally, the proposed shear strength equation was verified by the test results and compared with other shear strength equations.